E-conversa - Sá, Alexandre; Queiroz, Tania; da Costa, Carlos Eduardo Felix; Cavalcante, Daniele; Racy, João Paulo; Notari, Juliana (Revista Concinnitas, 2020)
Conversa realizada por e-mail, iniciada em 01/04/2020 e concluída em 24/07/2020